2002
DOI: 10.1046/j.1365-2672.2002.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an enzyme assay for rapid assessment of Escherichia coli in seawaters

Abstract: Aims: An analytical protocol has been developed and applied for the detection of glucuronidase activity in marine waters as a rapid alternative approach to assess the microbiological quality of seawaters. Methods and Results: The fluorogenic substrate 4-methylumbelliferyl-b-D-glucuronide is cleaved to a fluorescent product, methylumbelliferone, by the enzyme b-glucuronidase, specific to Escherichia coli and closely related enterobacterial species (Shigella). The results suggest that this test is related to E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 18 publications
5
33
0
Order By: Relevance
“…The high levels of activity observed in some cultures may indicate that their starved metabolic state lead to an increase in bacterial enzymatic activities hydrolyzing the fluorogenic substrate rapidly. Caruso et al (2002) reported that full development of enzymatic activities start at lag phase and is required for the enzyme expression.…”
Section: Figure 2: Time Series Hydrolyses Of Mug By Different Concentmentioning
confidence: 99%
See 4 more Smart Citations
“…The high levels of activity observed in some cultures may indicate that their starved metabolic state lead to an increase in bacterial enzymatic activities hydrolyzing the fluorogenic substrate rapidly. Caruso et al (2002) reported that full development of enzymatic activities start at lag phase and is required for the enzyme expression.…”
Section: Figure 2: Time Series Hydrolyses Of Mug By Different Concentmentioning
confidence: 99%
“…Enzyme activities are subject to the physiological status of bacteria and that under nutritional and light stresses, a fraction of cells may gradually lose its culturability, although remaining metabolically active (Caruso et al 2002). Besides, E. coli β-Dglucuronidase (GUD) activities are very sensitive to temperature.…”
Section: Reagents and Assay Conditionsmentioning
confidence: 99%
See 3 more Smart Citations